PREDICTION OF CONTACT FORCE AT MEDIAL KNEE POINT - Hassan, Nawar Banwan (Journal of medical and pharmaceutical sciences, 2018)
(KCF) Knee contact force is one of important expressive parameters to evaluate function of prediction knee joint. The study aimed to investigate whether the predicted forced will effect on knee joint and how can reduce the force of knee joint pressure while walking and running. The better understanding of the complex mechanism and its resulting joint kinematics allows a better elucidation of the mechanisms behind body growth, aging progression. Data conquest to patient with data of height 168 cm, weight 66.7 kg, knee side of right and shoes are Rockport’s flat bottom sneakers. We observed altered muscle force ranges. The result shown that, The overall quantitative assessment revealed an average square root error ranging from 5.5 to 189.1 N. The present study showed an important variation of kinematical and muscle force behaviors under the voluntary altered gait patterns. The researcher conclusion shown that the simulation result of useful information could allow a better understanding of the joint function design and muscle leading to deeper knowledge of joint and muscle mechanisms related to neural commands.